Protective effects of kefir against zearalenone toxicity mediated by oxidative stress in cultured HCT-116 cells. (January 2019) - El Golli-Bennour, Emna; Timoumi, Rim; Koroit, Meriam; Bacha, Hassen; Abid-Essefi, Salwa
Abstract: Kefir is a fermented milk with numerous health favors counting restorative properties of bacterial flora, reduction of the symptoms of lactose intolerance, immune system stimulation, cholesterol reduction, as well as anti-mutagenic and anti-tumor properties. Zearalenone (ZEN) is a mycotoxin produced by some Fusarium species. ZEN often occurs as a contaminant in cereal grains and animal feeds. Human exposure occurs by ingestion of mycotoxin-contaminated products and can cause serious health problems. This study aimed to assess the preventive effect of kefir against ZEN toxicity in cultured HCT-116 colorectal carcinoma cells; by the evaluation of cell viability, oxidative stress status and the initiation of apoptotic cell death pathway. Our results demonstrated that ZEN inhibits cell proliferation which was accompanied by an increase in the generation of free radicals as measured by fluorescent 2, 7-dichlorofluorescein (DCF) and Malondialdehyde (MDA). As an adaptive response to this redox status, we showed an induction of heat shock protein expression (Hsp 70) and an activation of antioxidant enzymes; catalase and Superoxide Dismutase (SOD). Moreover, a loss of mitochondrial membrane potential (Δѱm) was observed. The co-treatment as well as the pre-treatment by kefir showed a reduction of ZEN induced damages for all tested markers. However, the pre-treatment seems to be the most efficient, it prevented almost all ZEN hazards. Consequently, oxidative damage appears to be a key determinant of ZEN induced toxicity in cultured HCT-116 cells. In conclusion, we showed that kefir may better exert its virtue on preventive mode rather than on curative one. By this way, kefir as a beverage with highly antioxidant properties could be relevant particularly with the emergent demand for natural products which may counteract the detrimental effects of oxidative stress and therefore prevent multiple human diseases. Highlights: Zearalenone inhibition of HCT-116 cell proliferation was accompanied by a perturbation in oxidative stress status. An increase in the generation of free radicals, Hsp 70 expression and antioxidant enzyme activations was observed. Kefir treatment reduced efficiently ZEN inducing cell mortality, oxidative damage and apoptotic signaling pathway initiation. Kefir pre-treatment protective effects were more efficient than the effects on co-treatment mode. This study constitutes the first report on the evaluation of whole kefir beverage preventive effects on cultured cells.